Hypselodoris jacksoni, a new species from the south-western Pacific Ocean (Nudibranchia: Chromodorididae), with a discussion on intraspecific variation in mantle glands in Chromodoris willani Rudman, 1982 - Wilson, Nerida G.; Willan, Richard C. (Zootaxa, 2007)
A new species of Hypselodoris (Chromodorididae) is described from the subtropical and temperate south-western Pacific Ocean (eastern Australia, Lord Howe Island, Norfolk Island). The colouration of Hypselodoris jacksoni sp. nov. is distinctive, though highly variable intraspecifically. Hypselodoris jacksoni belongs to the Indo-Pacific Hypselodoris clade (for which the key synapomorphy is a minute receptaculum seminis) and, based on comparisons of internal and external morphology, appears to belong to a subclade characterised by an elevated branchial sheath, probably most closely related to H. krakotoa Gosliner & Johnson, 1999, H. reidi Gosliner & Johnson, 1999 and H. regina Ev. & Er. Marcus, 1970. Intraspecific variation in the arrangement of mantle glands in H. jacksoni prompted a preand post-fixation comparison of mantle glands in another chromodorid, Chromodoris willani Rudman, 1982. These results indicate these structures can vary significantly within a population (and thus species), and it is likely that too much emphasis has been placed on mantle glands for separating species in the recent literature.